2018
DOI: 10.1038/s41598-018-34120-4
|View full text |Cite
|
Sign up to set email alerts
|

Target-distractor competition cannot be resolved across a saccade

Abstract: When a distractor is presented in close spatial proximity to a target, a saccade tends to land in between the two objects rather than on the target. This robust phenomenon (also referred to as the global effect) is thought to reflect unresolved competition between target and distractor. It is unclear whether this landing bias persists across saccades since a saccade displaces the retinotopic representations of target and distractor. In the present study participants made successive saccades towards two saccadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
10
2
Order By: Relevance
“…While the persistence of the global effect in double-step saccades (Arkesteijn et al, 2018) could have been because participants had preprogrammed a saccade, this explanation was not supported by results obtained in the present study. The similarity of the time course of the global effect in the conditions when the identity of the target was known in advance or only revealed later is remarkable.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…While the persistence of the global effect in double-step saccades (Arkesteijn et al, 2018) could have been because participants had preprogrammed a saccade, this explanation was not supported by results obtained in the present study. The similarity of the time course of the global effect in the conditions when the identity of the target was known in advance or only revealed later is remarkable.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with a previous study (Arkesteijn et al 2018), where a global effect was found in a double-step memory-guided saccade, together with a sustained global effect as a function of saccade latency. The magnitude of the global effect for the double-step memoryguided saccades was smaller than for the single memoryguided saccades reported here (8% bias in the direction of the distractor in the previous study, compared with 20% bias reported in the present study).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations